Sergio Ramírez, political culture and the rescue of the historic Sandino - Maciel, Fred [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2018)
The article intends to present some appropriations and elaborations made since the emergence of the Nicaraguan revolutionary process, having as main reference the figure of Augusto C. Sandino. Recognizing the existence of a wide Sandinista political culture, the work and writings of Sergio Ramírez gain prominence, especially in the evocation of a historical Sandino, with ethical and human bias. Thus, we will discuss the development of some of these constructions, as well as their progress, highlighting the breadth and diversity of Sandinismo as an important cultural and political force in Nicaragua since the mid-20th century.
Sergio Ramírez, cultura política e o resgate do Sandino histórico
Keywords: Nicaragua; Sandinismo; Sandino; Sergio Ramírez